Evidence against lexicalist or configurational approaches to structural encoding in sentence production - Baumann, Michael; Pappert, Sandra; Pechmann, Thomas (The syntax of argument structure, 2021)
Das Kapitel Evidence against lexicalist or configurational approaches to structural encoding in sentence production erschien in The Syntax of Argument Structure auf Seite 33.